Carboxymethylpsyllium (CMPsy)/poly(acrylamide)(poly(AAm)) hydrogels for oral delivery of anti-diabetic drug Gliclazide. Issue 4 (3rd April 2017) - Bajpai, S. K.; Chand, Navin; Agrawal, A.
ABSTRACT: In this work, controlled release of anti-diabetic drug Gliclazide (Glz) from the carboxymethylpsyllium (CMPsy)/poly(acrylamide) (poly (AAm)) semi-interpenetrating networks (Semi-IPN) has been studied under physiological conditions. The semi-IPN was characterized by TGA, XRD and FTIR analysis. The release of drug Glz was observed to increase with concentration of drug entrapped in the hydrogels but varied inversely with the degree of crosslinking of the semi-IPN. The release data were analyzed using various kinetic models. Finally, the in-vivo investigation of efficacy of Gliclazide–loaded semi-IPN was carried out on Albino wistar rats . The formulation demonstrated fair effectiveness in reducing the glucose level, even at an oral administration frequency of once every alternate day.